Serlopitant reduced pruritus in patients with prurigo nodularis in a phase 2, randomized, placebo-controlled trial - Ständer, Sonja; Weisshaar, Elke (Journal of the American Academy of Dermatology, 2019)
BACKGROUND: Anecdotal evidence suggests that neurokinin 1 receptor antagonism reduces pruritus intensity in chronic pruritic conditions such as prurigo nodularis (PN). - OBJECTIVE: This study assessed safety and efficacy of the neurokinin 1 receptor antagonist serlopitant for treatment of pruritus in PN. - METHODS: In this randomized, double-blind, placebo-controlled study, 128 patients with chronic, treatment-refractory PN for more than 6 weeks received serlopitant, 5 mg, or placebo orally once daily for 8 weeks. The primary end point was change in average itch visual analog scale score at weeks 4 and 8. - RESULTS: Average itch visual analog scale scores significantly improved with serlopitant versus with placebo at weeks 4 and 8: the least squares mean difference (serlopitant minus placebo) was -1.0 at week 4 (P = .02) and -1.7 at week 8 (P < .001). The least squares mean difference between serlopitant and placebo reached statistical significance at week 2 (-0.9 [P = .011]). The most frequently reported treatment-emergent adverse events in the serlopitant group were nasopharyngitis, diarrhea, and fatigue. - LIMITATIONS: The 8-week duration may be insufficient to assess clinically relevant resolution of PN lesions. - CONCLUSIONS: Serlopitant reduced pruritus in patients with treatment-refractory PN and was well tolerated.